#TITLE_ALTERNATIVE# - LEONARDO SIMATUPANG (10502015), RIZAL
Metal oxide materials are known to have many interesting properties. It can be mentioned here such as semiconducting, catalytic and optical properties. These interesting properties then draw people's attention to study the oxide materials. Titanium dioxide with chemical formula of TiO2 also has many important properties and can be applied as photocatalyst. The physical and chemical properties of oxide materials depend on its structural properties. The structural properties can be affected by the synthesis method. In this project, the application of electric field during synthesis of oxide materials as one of modification technique is studied in order to modify the crystal structure and its physical properties. In particular, the study was focused on the effect of the electric field on the structure, morphology, physical and chemical properties of TiO2. The synthesis method used in this study is the chemical solution methods, which Ti cations were hydrolyzed to form titanium dioxide. The maximum applied electric field during synthesis is 2 kV cm-1. The resulted product synthesized with electric field shows that the absorbance peak shifts to the smaller wave length. This means that the energy gap of TiO2 larger than the energy gap of TiO2 synthesized without electric field. Meanwhile, the X-ray diffraction measurement shows that the electric field effect tends to make lower intensity of the crystalline peak indicated sample tends to have an amorphous structure. This is supported by the scanning electron microscope images, which show smaller grain size of TiO2 prepared with external electric field. This method can be used in the synthesis and modification of another oxide compounds.